2021
DOI: 10.1017/s1368980021003232
|View full text |Cite
|
Sign up to set email alerts
|

Determining the nutritional immunity information-seeking behaviour during the COVID-19 pandemic in India: a Google Trends data analysis

Abstract: Objective: During COVID-19, the internet was a prime source for getting relevant updates on guidelines and desirable information. The objective of the present study was to determine the nutritional immunity information seeking behaviour during COVID-19 in India. Design: Google Trends (GTs) data on relevant COVID-19 and nutritional topics were systematically selected and retrieved. Data on newly reported COVID-19 cases were also examined on a daily basis. The cross-correlation method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
(26 reference statements)
2
7
0
Order By: Relevance
“…Our research work demonstrates the potential of analyzing user activity collected through Google and GT. Our results concur with those of prior research ( 33 , 36 , 40 , 43 ), and it emphasizes the importance of OHISB evaluation in current days for raising public awareness of specific health issues ( 37 , 40 45 ). Furthermore, our study is novel as it evaluates the impact of OHISB on the WDMD considering selected European countries and depending on whether they have NPHs or not, their healthcare system model, and the prevalence of DM among the population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our research work demonstrates the potential of analyzing user activity collected through Google and GT. Our results concur with those of prior research ( 33 , 36 , 40 , 43 ), and it emphasizes the importance of OHISB evaluation in current days for raising public awareness of specific health issues ( 37 , 40 45 ). Furthermore, our study is novel as it evaluates the impact of OHISB on the WDMD considering selected European countries and depending on whether they have NPHs or not, their healthcare system model, and the prevalence of DM among the population.…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, Google Trends (GT) ( 34 ) is becoming a tool that is raising special interest for probable forecasts and in understanding the interests of the population ( 35 ). Data provided by GT can be used as a “surrogate” of online health information seeking behavior (OHISB) and give useful information on search behaviors related to health or healthy habits ( 33 , 36 38 ). Some research examines the association between data provided by internet sources and public health policies ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings that associate increased interest in nutrition with greater diet-nutrition information seeking and more frequent dietary change complement other data from the same time period evidencing unprecedented search-engine query volumes related to diet and nutrition [ 130 , 131 ], paralleled with record-high food supplement sales [ 132 ] and diverging swings in healthier/unhealthier eating practices during home confinements [ 133 , 134 , 135 ].…”
Section: Discussionsupporting
confidence: 79%
“…Compared to the period before the COVID-19 pandemic, RSVs of vitamins, particularly vitamin C, increased significantly after the pandemic outbreak [ 27 ]. Kushwaha and colleagues also found that daily new COVID-19 cases in India were highly correlated to search terms related to immune-related nutrients, including “multivitamin”, “nutrients”, and “vitamin” in different time lag days by using cross-correlation analysis [ 43 ]. In our results, the interests in nutritional supplements were influenced by the time before new COVID-19 cases and deaths occurred.…”
Section: Discussionmentioning
confidence: 99%